The Impact of Team Learning Climate on Innovation Performance – Mediating role of knowledge integration capability - Li, Ming-Shun; Li, Jiaqi; Li, Jia-Mei; Liu, Zi-Wei; Deng, Xin-Tao (Frontiers in Psychology, 2023)
To address the fierce competition for corporate innovation in the digital economy, this study introduces knowledge integration capability as a mediating variable in light of social information processing theory, and explores the mechanism of team learning climate on innovation performance. Data were collected from a sample of 184 team members for statistical analysis, and Statistical methods such as descriptive statistical analysis, correlation analysis, and regression analysis were used to verify the study hypotheses through SPSS and Amos software, and the results showed that: (1) Team learning climate has a significant positive effect on knowledge integration capability. (2) Team learning climate has a significant positive effect on innovation performance. (3) Knowledge integration capability has a significant positive effect on innovation performance. (4) Knowledge integration capablity partially mediates the role between team learning climate and innovation performance. The results proved the perspective of knowledge integration capability for the mechanism of team learning climate on innovation performance from the perspective of knowledge integration capability, and provided theoretical references for creating a learning climate in companies to promote members’ knowledge learning and enhance innovation performance.